Life-cycle cost assessment of vertical structures under nonstationary winds: Downburst vs. tornado loads. (15th September 2021) - Le, Viet; Caracoglia, Luca
Highlights: Structural effects of nonstationary wind loads (tornadoes, thunderstorms) are studied. A general framework to assess performance capacity of tall structures is proposed. Various model of tornado and thunderstorm wind fields are implemented. New model for assessing the thunderstorm arrival rate is proposed. Systematic comparison of life-cycle cost results between the two hazards is conducted. Abstract: The continued development of performance-based wind engineering (PBWE) has led to the application of life-cycle cost assessment (LCCA) as a means to evaluate the risks and consequential losses over a structure's lifetime from damages caused by large-scale wind phenomena, such as synoptic storms and hurricanes. However, the advancement of this analytical tool with regard to non-synoptic, nonstationary windstorms such as downbursts and tornadoes has so far been lacking due to incomplete knowledge of either the wind fields or their induced fluid-structure forces. In this study, a methodology is proposed that extends PBWE and LCCA to characterize structural damages with respect to hazard parameters, describing these wind phenomena, and subsequently to quantify and compare the relative monetary losses that are incurred. The dynamics of two vertical structures subjected to wind loads of various intensities using multiple downburst and tornado wind field models and data from wind tunnel experiments will be analyzed. Key components of the methodology are tailored in the holistic framework to consider the risks and consequences posed by these nonstationary windstorms.